A Green Fist in a Velvet Glove: The Ecological State and Sustainable Development. (1st November 2001) - Lundqvist, L.J.
Suggestions for transforming ecological sustainability into operative social choice mechanisms can be viewed through the bifocal lens of limits on, and opportunities for, the ecological state. Using lines of reasoning brought in from the comparative study of environmental policy, this article tries to stake out how far the ecological state can go in pursuing objectives of sustainable development without intruding on values and objectives fundamental to democracy. The article discusses social choice mechanisms in terms of the ecological state's authority, management capacities, effectiveness, and legitimacy, drawing up the image of the ecological state as a 'green fist in a velvet glove' with the ultimate objective of integrating 'ecological' evaluations into the public mind so that they become as 'natural' as those 'economic' criteria presently applied. Concluding that such 'ecological' consciousness involves a great leap in ecological information processing and dissemination within and throughout societies, the article invokes the sustainability and success of democratic social welfare states which base authoritative command on enlightened debate and deliberation as evidence that such a leap can be successfully made through processes of informed consensus.